Psychosocial conditions during school-age as determinants of long-term labour market attachment: a study of the Northern Swedish Cohort from the 1980s to the 2020s - Pekka Virtanen; Tapio Nummi; Urban Janlert; Anne Hammarström (BMC, 2024)
Abstract Background This study, conducted on a Swedish population cohort, explores how internalized (depressive and functional somatic) and externalized (smoking, drinking, truancy, vandalism, delinquency) mental health symptoms, as well as close interpersonal relations (family climate and school connectedness) reported during adolescence, influence the work-life course up to late midlife. Methods We examined repeated measurements of labour market status from age 16 to 56 using sequence analyses. We identified five different labour market attachment (LMA16-56) trajectories, namely 'strong,' 'early intermediate,' 'early weak,' 'late weak,' and 'constantly weak.' Multinomial logistic regressions were employed to relate each of the nine determinants to the identified trajectories. Results When compared to the risk of 'strong' LMA16-56, adversity in all conditions, except for vandalism, entailed a higher risk of the 'constantly weak' trajectory. Moreover, all conditions, except for functional somatic symptoms, entailed a higher risk of the 'late weak' LMA16-56. The risk of the 'early intermediate' LMA16-56 was non-significant across all the conditions. Conclusions This study contributes to existing knowledge through its novel exploration of labour market attachment and the revelation of the significance of proximal interpersonal relationships in attachment outcomes. Additionally, the study reaffirms the importance of externalizing behaviour, while suggesting that internalized symptoms in adolescence might have a less influential, though not negligible, role. These results underscore the importance of addressing acting out behaviour and nurturing human relationships during compulsory basic education, when the entire age group is still within reach. This approach aims not only to reduce frictions in the school-to-work transition but also to prevent midlife labour market attachment problems that may arise with delayed intervention.